Intellectual Rights in the Light of the Qurʾan and Universal Declaration of Human Rights - Alhaj, Thabet Ahmad Abdallah Abu (Al-Bayān, 2023)
Human Intellectual Rights in the Qurʾan is a necessary extension of its respect for the value of human beings. It is regarded as an instrument with the primary purpose to guide one to happiness in this world and the Hereafter. Based on the belief that Islam is a religion applicable to all in every circumstance, we selected Sample of Qurʾanic verses to illustrate how Islam perceives and defends intellectual Rights. The study aims to clarify the types of intellectual rights that Qurʾan granted to humans and to be a direct response to those who perceive Islam as a religion of repression, inertia, and hyperbole. The author notes that the freedoms admitted in the Qurʾan are not absolute, but constrained by methodological and moral principles, taking into consideration the interests of the individual and the community while also avoiding extremism and negligence. The study’s comparison between the freedoms granted by the Qurʾan to Intellectual Rights and such as exist in the Universal Declaration of Human Rights, is based on rational standards, and not only on religious texts. This is achieved by identifying the theoretical and practical applications of the freedom of Intellectual Rights in the Qurʾan and Universal Declaration of Human Rights, and their implications. The study found that the Universal Declaration of Human Rights failed to achieve human dignity and preserve communities’ rights and freedoms due to its insistence of the absolute freedom of thought, belief, and expression. Such freedoms were not subject to controls and were not provided with direction. The theoretical grounds upon which these freedoms were articulated were flawed leading to gross abuses in practical reality.